Early Plasma Nuclear DNA, Mitochondrial DNA, and Nucleosome Concentrations Are Associated With Acute Kidney Injury in Critically Ill Trauma Patients. (28th March 2022) - Faust, Hilary E.; Oniyide, Oluwatosin; Wang, Yiyue; Forker, Caitlin M.; Dunn, Thomas; Yang, Wei; Lanken, Paul N.; Sims, Carrie A.; Yehya, Nadir; Christie, Jason D.; Meyer, Nuala J.; Reilly, John P.; et al.
Abstract : OBJECTIVES: Circulating nucleic acids, alone and in complex with histones as nucleosomes, have been proposed to link systemic inflammation and coagulation after trauma to acute kidney injury (AKI). We sought to determine the association of circulating nucleic acids measured at multiple time points after trauma with AKI risk. DESIGN: We conducted a prospective cohort study of trauma patients, collecting plasma on presentation and at 6, 12, 24, and 48 hours, defining AKI over the first 6 days by Kidney Disease Improving Global Outcomes serum creatinine and dialysis criteria. We determined kinetics of plasma mitochondrial DNA (mtDNA), nuclear DNA (nDNA), and nucleosome levels across time points and associations with AKI using multivariable linear mixed-effects models, adjusted for injury characteristics and blood transfusions. We evaluated the association of presentation nucleic acid damage-associated molecular patterns (DAMP) concentrations with subsequent AKI, adjusting for injury severity using multivariable logistic regression. SETTING: Academic level I trauma center. PATIENTS: Trauma patients ( n = 55) requiring intensive care for greater than or equal to 24 hours after presentation. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: AKI developed in 17 patients (31%), a median of 12.0 hours (interquartile range, 6.2–24.1 hr) after presentation. mtDNA demonstrated a time-varying association with AKI ( p = 0.022, interaction with time point), with differences by AKI status not emerging until 24 hours (β = 0.97 [95% CI, 0.03–1.90] log copies/uL; p = 0.043). Patients who developed AKI had higher nDNA across all time points (overall β = 1.41 log copies/uL [0.86–1.95 log copies/uL]; p < 0.001), and presentation levels were significantly associated with subsequent AKI (odds ratio [OR], 2.55 [1.36–4.78] per log copy/uL; p = 0.003). Patients with AKI had higher nucleosome levels at presentation (β = 0.32 [0.00–0.63] arbitrary unit; p = 0.048), a difference that was more pronounced at 24 hours (β = 0.41 [0.06–0.76]; p = 0.021) and 48 hours (β = 0.71 [0.35–1.08]; p < 0.001) ( p = 0.075, interaction with time point). CONCLUSIONS: Plasma nucleic acid DAMPs have distinct kinetics and associations with AKI in critically ill trauma patients. nDNA at presentation predicts subsequent AKI and may be amenable to targeted therapies in this population.